2009
DOI: 10.1055/s-0029-1220789
|View full text |Cite
|
Sign up to set email alerts
|

Placental Laser Surgery for Severe Previable Feto-fetal Transfusion Syndrome in Triplet Gestation

Abstract: Information on feto-fetal transfusion syndrome (FFTS) in higher-order multifetal gestation is limited. We report outcomes of 10 triplet pregnancies treated by fetoscopic laser occlusion of the chorioangiopagous vessels (FLOC). The study period was August 1992 to August 2008. Inclusion criteria were gestational age < or =25 weeks and ultrasound confirmation of monochorionicity in at least one twin set and FFTS. Treatment included FLOC, exit amnioreduction, and cerclage when indicated. Hospital records, placenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Although based on small numbers, these results strongly suggest that laser coagulation is preferable to expectant management or amniodrainage [17]. Five successful cases of MC triplet gestations (with 3 survivors) treated with laser coagulation were reported (including the cases in our study) [2,7,8,9,10,21], but 11 other cases were not successful.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Although based on small numbers, these results strongly suggest that laser coagulation is preferable to expectant management or amniodrainage [17]. Five successful cases of MC triplet gestations (with 3 survivors) treated with laser coagulation were reported (including the cases in our study) [2,7,8,9,10,21], but 11 other cases were not successful.…”
Section: Discussionmentioning
confidence: 58%
“…From 1990 to 2010, 22 articles met the inclusion criteria and we identified 25 MC and 97 DC triplet pregnancies with TTTS [2,3,6,7,8,9,10,11,12,13,14,15,16,17,18,19,21,22,23,24,25]. Quintero stage, in the reported cases including the cases in this study, was stage I in 7% (2/27) stage II in 15% (4/27), stage III in 45% (12/27) and stage IV in 33% (9/27) of the MC triplets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search identified 5 previous studies reporting data on MCTA pregnancies with FFTS treated by endoscopic laser surgery, and the combined data from these studies with ours are shown in table 3 and figure 2 [10][11][12][13]15] . In a total of 29 such pregnancies, the pooled survival rate of at least one baby was 80.6% (95% CI 64.9-92.4), and the overall survival for all babies was 57.5% (95% CI 36.2-77.4); there was significant heterogeneity between the studies.…”
Section: Synthesis With Results From Previous Studiesmentioning
confidence: 99%
“…In sFGR with abnormal Doppler findings in the umbilical artery of the affected fetus, there is a high risk of perinatal death and handicap for both twins; the management for affected pregnancies presenting at midgestation includes endoscopic laser coagulation of the inter-twin communicating placental vessels or cord occlusion of the FGR twin [4][5][6][7][8] . Few studies in a small number of patients have reported on endoscopic laser coagulation of communicating placental vessels for the management of FFTS in MC or dichorionic (DC) triamniotic (TA) triplet pregnancies complicated by FFTS [9][10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%